ACEH CULTURAL CENTER WITH CONTEMPORARY ARCHITECTURE APPROACH IN BANDA ACEH - Andalucia, Andalucia; Fadhil , Muhammad (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
This project aims to design the Aceh Regional Cultural Arts Center in Banda Aceh City using a contemporary architectural approach. The main objective of this study is to integrate the cultural values and unique traditions of Aceh into the design of modern architecture that reflects both local and global identities. The research method involves in-depth analysis of the cultural context of Aceh, identification of significant elements of traditional culture, and the development of a contemporary architectural concept that combines the richness of cultural heritage with modern aspects. The design of the Cultural Arts Center includes the utilization of traditional elements such as ornaments and spatial layouts that support the promotion and preservation of traditional arts and culture. Meanwhile, the contemporary architectural approach is reflected in the selection of modern materials and technology, aiming to create an energy-efficient and sustainable building. The results of this research are expected to provide guidance for architects and policymakers in initiating and developing similar cultural art projects in other regions with unique cultural heritage. The Aceh Regional Cultural Arts Center in Banda Aceh is expected to serve as an example of the harmonious integration of local cultural heritage and modern values within the context of contemporary architecture.